Dynein regulates epithelial polarity and the apical localization of stardust A mRNA. - Sally Horne-Badovinac; David Bilder (PLoS Genetics, 2008)
Intense investigation has identified an elaborate protein network controlling epithelial polarity. Although precise subcellular targeting of apical and basolateral determinants is required for epithelial architecture, little is known about how the individual determinant proteins become localized within the cell. Through a genetic screen for epithelial defects in the Drosophila follicle cells, we have found that the cytoplasmic Dynein motor is an essential regulator of apico-basal polarity. Our data suggest that Dynein acts through the cytoplasmic scaffolding protein Stardust (Sdt) to localize the transmembrane protein Crumbs, in part through the apical targeting of specific sdt mRNA isoforms. We have mapped the sdt mRNA localization signal to an alternatively spliced coding exon. Intriguingly, the presence or absence of this exon corresponds to a developmental switch in sdt mRNA localization in which apical transcripts are only found during early stages of epithelial development, while unlocalized transcripts predominate in mature epithelia. This work represents the first demonstration that Dynein is required for epithelial polarity and suggests that mRNA localization may have a functional role in the regulation of apico-basal organization. Moreover, we introduce a unique mechanism in which alternative splicing of a coding exon is used to control mRNA localization during development.